In vitro and in vivo evaluation of the trypanocidal activity of the acetone extract of lichen Usnea steineri and its chemical constituents - Luiz Antonio Ferreira; Daniele da Silva Ferreira; Marcos Gomide Tozatti; Marcelly Canuto de Almeida Silva; Milton Groppo; Lizandra Guidi Magalhães; Márcio Luis Andrade e Silva; Ana Helena Januário; Patrícia Mendonça Pauletti; Leonardo Bindelli Verly; Mário F. C. Santos; Wilson Roberto Cunha (Natural Product Research, 2026)

Addendum: Electron microbeam investigations of the spent ash from the pilot-scale acid extraction of rare earth elements from a beneficiated Kentucky fly ash (2025, Int. J. Coal Geol. 303, 104738): Further consideration of particle-size reduction from feed to processed fly ash - Debora Berti; Anne E. Oberlink; John G. Groppo; Prakash Joshi; Dorin V. Preda; David P. Gamliel; Todd Beers; Michael Schrock; Shelley D. Hopps; Tonya D. Morgan; Bernd Zechmann; James C. Hower (International Journal of Coal Geology, 2026)

Filling the gap in the UHP metamorphic record of the Liguro-Piemont Lower unit: Insights on fluid-mediated formation of atoll garnets - A. Maffeis; A. Petroccia; S. Nerone; F. Caso; A. Corno; M. Bonazzi; F. Boero; S. Corvò; S. Ghignone; C. Groppo (Lithos, 2025)

Electron microbeam investigations of the spent ash from the pilot-scale acid extraction of rare earth elements from a beneficiated Kentucky fly ash - Debora Berti; John G. Groppo; Prakash Joshi; Dorin V. Preda; David P. Gamliel; Todd Beers; Michael Schrock; Shelley D. Hopps; Tonya D. Morgan; Bernd Zechmann; James C. Hower (International Journal of Coal Geology, 2025)

UHP metamorphism, decompression anatexis and retrogression of garnet-bearing metagranite and granitic gneiss from the Dabie orogen during continental collision - Cheng-Wei Zhang; Yang Yang; Yi-Can Liu; C. Groppo; F. Rolfo (Lithos, 2023)

Was coal metamorphism an influence on the minor element chemistry of the Middle Pennsylvanian Springfield (No. 9) coal in Western Kentucky? - James C. Hower; John G. Groppo; Cortland F. Eble; Shelley D. Hopps; Tonya D. Morgan (International Journal of Coal Geology, 2023)

ATLANTIC POLLINATION: a data set of flowers and interaction with nectar‐feeding vertebrates from the Atlantic Forest - Joice Iamara‐Nogueira; Natália Targhetta; Gina Allain; Adriano Gambarini; Alessandra R. Pinto; Ana Maria Rui; Andréa C. Araújo; Ariadna Lopes; Brenda Pereira‐Silva; Bruna Bertagni de Camargo; Caio Graco Machado; Caio Missagia; et al. (Ecology, 2022)
Flowering plant species and their nectar‐feeding vertebrates exemplify some of the most remarkable biotic interactions in the Neotropics. In the Brazilian Atlantic Forest, several species of birds (especially hummingbirds), bats, and non‐flying mammals, as well as one lizard feed on nectar, often act as pollinators and contribute to seed output of flowering plants. We present a dataset containing information on flowering plants visited by nectar‐feeding vertebrates and sampled at 166 localities in the Brazilian Atlantic Forest. This dataset provides information on 1902 unique interactions among 515 species of flowering plants and 129 species of potential vertebrate pollinators and the patterns of species diversity across latitudes. All plant–vertebrate interactions compiled were recorded through direct observations of visits, and no inferences of pollinators based on floral syndromes were included. We also provide information on the most common plant traits used to understand the interactions between flowers and nectar‐feeding vertebrates: plant growth form, corolla length, rate of nectar production per hour in bagged flowers, nectar concentration, flower color and shape, time of anthesis, presence or absence of perceptible fragrance by human, and flowering phenology as well as the plant’s threat status by International Union for Conservation of Nature (IUCN) classification. For the vertebrates, status of threat by IUCN classification, body mass, bill or rostrum size are provided. Information on the frequency of visits and pollen deposition on the vertebrate’s body is provided from the original source when available. The highest number of unique interactions is recorded for birds (1771) followed by bats (110). For plants, Bromeliaceae contains the highest number of unique interactions (606), followed by Fabaceae (242) and Gesneriaceae (104). It is evident that there was geographical bias of the studies throughout the southeast of the Brazilian Atlantic Forest and that most effort was directed to flower–hummingbird interactions. However, it reflects a worldwide tendency of more plants interacting with birds compared with other vertebrate species. The lack of similar protocols among studies to collect basic data limits the comparisons among areas and generalizations. Nevertheless, this dataset represents a notable effort to organize and highlight the importance of vertebrate pollinators in this hotspot of biodiversity on Earth and represents the data currently available. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or scientific events.

Algae-Based Beneficial Re-use of Carbon Emissions Using a Novel Photobioreactor: a Techno-Economic and Life Cycle Analysis - Michael H. Wilson; Aubrey Shea; John Groppo; Czarena Crofcheck; David Quiroz; Jason C. Quinn; Mark Crocker (BioEnergy Research, 2021)

The antimetastatic drug NAMI-A potentiates the phenylephrine-induced contraction of aortic smooth muscle cells and induces a transient increase in systolic blood pressure - M. Vadori; C. Florio; B. Groppo; M. Cocchietto; S. Pacor; S. Zorzet; L. Candussio; G. Sava (JBIC Journal of Biological Inorganic Chemistry, 2015)

Bioactivity of Pelargonium graveolens essential oil and related monoterpenoids against sweet potato whitefly, Bemisia tabaci biotype B - Edson L. L. Baldin; Gabriela P. Aguiar; Thiago L. M. Fanela; Muriel C. E. Soares; Milton Groppo; Antônio E. M. Crotti (Journal of Pest Science, 2015)

Fragments of the Western Alpine Chain as Historic Ornamental Stones in Turin (Italy): Enhancement of Urban Geological Heritage through Geotourism - A. Borghi; A. d’Atri; L. Martire; D. Castelli; E. Costa; G. Dino; S. E. Favero Longo; S. Ferrando; L. M. Gallo; M. Giardino; C. Groppo; R. Piervittori; et al. (Geoheritage, 2014)

Plant-derived essential oils affecting settlement and oviposition of Bemisia tabaci (Genn.) biotype B on tomato - Edson L. L. Baldin; Antônio E. M. Crotti; Kamila A. L. Wakabayashi; José P. G. F. Silva; Gabriela P. Aguiar; Efrain S. Souza; Rodrigo C. S. Veneziani; Milton Groppo (Journal of Pest Science, 2013)

Circulation of different rhinovirus groups among children with lower respiratory tract infection in Kiremba, Burundi - S. Esposito; C. Daleno; E. Baggi; E. Ciarmoli; A. Lavizzari; M. Pierro; M. Semino; M. Groppo; A. Scala; L. Terranova; C. Galeone; N. Principi (European Journal of Clinical Microbiology & Infectious Diseases, 2012)